2021
DOI: 10.1002/anie.202111267
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Tricyclic Nitrogen Heterocycles by a Gold(I)‐Catalyzed Cascade Cyclization of Allenynes and Application to Polycyclic π‐Electron Systems

Abstract: An ovel approach to the direct construction of tricyclic nitrogen heterocycles based on gold-catalyzed cascade cyclization of aminoallenynes is described. The expected biscyclization reaction of hydroxyisobutyryl-protected aminoallenynes was efficiently promoted by ac atalytic amount of BrettPhosAuNTf 2 in the presence of iPrOH to produce 1,2dihydrobenzo[cd]indole derivatives in good yields.W hen the reaction was combined with Friedel-Crafts acylation or palladium-catalyzed N-arylation, the resulting tricyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 63 publications
3
13
0
Order By: Relevance
“…Fukazawa and Ohno group reported a gold‐catalyzed cascade cyclization of aminoallenynes 7 , a unique method for the direct construction of tricyclic nitrogen heterocycles (Scheme 3). [32] 5 mol% of BrettPhosAuNTf 2 was effectively used to promote the desired biscyclization reaction of hydroxyisobutyryl‐protected aminoallenynes 7 in the presence of i PrOH, yielding 1,2‐ dihydrobenzo[ c,d ]indole derivatives 8 in 46–82 %. The resultant tricyclic products were effectively transformed into nitrogen‐containing polycyclic aromatic compounds ( N‐PACs ) with strongly conjugated π ‐electron systems when the procedure was coupled with Friedel‐Crafts acylation or palladium‐catalyzed N ‐arylation.…”
Section: Single Cascade Reactionsmentioning
confidence: 99%
“…Fukazawa and Ohno group reported a gold‐catalyzed cascade cyclization of aminoallenynes 7 , a unique method for the direct construction of tricyclic nitrogen heterocycles (Scheme 3). [32] 5 mol% of BrettPhosAuNTf 2 was effectively used to promote the desired biscyclization reaction of hydroxyisobutyryl‐protected aminoallenynes 7 in the presence of i PrOH, yielding 1,2‐ dihydrobenzo[ c,d ]indole derivatives 8 in 46–82 %. The resultant tricyclic products were effectively transformed into nitrogen‐containing polycyclic aromatic compounds ( N‐PACs ) with strongly conjugated π ‐electron systems when the procedure was coupled with Friedel‐Crafts acylation or palladium‐catalyzed N ‐arylation.…”
Section: Single Cascade Reactionsmentioning
confidence: 99%
“…[4] We also found that the vinyl cation species can be trapped by a nitrogen nucleophile to produce tricyclic fused indoles 4 and pyrrolonaphthalenes 5 (Scheme 2B). [5] We next envisaged that the intramolecular arylation of vinyl cations might produce highly π-conjugated molecules with a strained structure.…”
mentioning
confidence: 99%
“…[63] In our ongoing endeavors in reaction development using gold catalysis, [42][43][44][45][46][47] we previously reported the synthesis of acenaphthenes 2, which can be rationalized by a 1,5-hydride shift on a vinyl cationic gold complex A generated from allenynes 1 (Scheme 1B). [64,65] From this vantage point, we envisioned that a 1,5-hydride shift leading to electrophilic α-imino gold carbene functionalization should also be conceivable in gold-catalyzed electrophilic C-H functionalization, leading to fused indoles such as 4 (Scheme 1C), which often exhibit biologically intriguing properties. [21] Herein we present our research to show that alkynylated arylazides are suitable substrates for gold-catalyzed cascade cyclizations to form indeno[b]-type fused indoles 4 via a 1,5-hydride shift on α-imino gold carbenes and C-cyclization.…”
mentioning
confidence: 99%